Battle hymn of the tiger mother - Chua, Amy. (Penguin Press, 2011)
Traces the rewards and pitfalls of a Chinese mother's exercise in extreme parenting, describing the exacting standards applied to grades, music lessons, and avoidance of Western cultural practices.